Analisis Kemampuan Menulis Teks Argumentasi Siswa Kelas IV Sekolah Dasar (International Forum of Researchers and Lecturers, 2025)
His study aims to analyze the ability of fourth grade elementary school stundents in writing argumentative texts. The study used a qualitative descriptive approach with an instrumen in the form of Student worksheet (LKPD) wich were developed to measure the skills of expressing opinions, giving reasons, and making consclusions in the form of argumentative texts. The result of the study showed that most students were able to express oponions and reason simply, but still had difficulty in comosing coherent and coherent paraghraphs. This study provides an overview of the importance of continuous practice in writing arguments for elementary sschool students.